Pemodelan Kepuasan Pelanggan ShopeeFood Berbasis Webqual 4.0 dan Metode Kano - Oktiviana Perangin-angin; Jay Idoan Sihotang (TeIKa, 2023)
The development of technology today allows many people to be able to maximize the use of the internet in meeting their daily needs. One of the applications used is Shopee with the Shopee Food service which offers many promos and various food options. The purpose of this research was to see the effect of the attributes in Webqual 4.0 on the projection of the Kano Model regarding customer satisfaction with ShopeeFood services. In this case, the researcher will conduct research on Indonesian Adventist University students as respondents to the research. The division of the questionnaire is divided into two main parts, namely the webqual method questionnaire which assesses the reality and expectations of the service, and the Kano model which assesses the functionality, dysfunctionality and importance of each feature or attribute. The results of the research show that the respondents were satisfied with the ShopeeFood service with a score of the Usability aspect with a score of 4.15, Information Quality with a value of 4.02, and Service Interaction Quality with a value of 4.00. The results of webqual data processing are supported by the results of the kano model questionnaire data processing. Where satisfaction with the ShopeeFood service is reflected in the presence of several features/attributes that meet the expectations of users. Overall, each feature/attribute is included in the Attractive category (A).